Summary of the Evaluation Studies 1960-61 - Planning Commission (Planning Commission, 1961)
In chawing up the programme of the P.E.O. for 1960-61, a significant departure was made from the earlier practice of relating evaluation essentially and solely to the community development programme or particular aspects of it. It was decided by the Planning Commission that the scope of the P.E.O. studies should be extended so as to cover rot only the community development programme but also other programmes included in the plan for the development of agriculture and the rural sector. The specific programmes selected for detailed evaluation in 19G0-G1 were minor irrigation, improved seed, the training and role of Gram Saha yaks and irrigation from some of the major projects. Reports on the first three studies were submitted to the Annual Conference on Community Development held al Hyderabad in July, 1961. These have been brought out separately; and their summary is presented in this volume.
Programme Evaluation Organisation Planning Commission Government of India